Pengaruh Feed Rate Terhadap Uji Kekerasan, Uji Tarik dan Mikro Struktur Pada Alumunium 6061 dengan Metode Friction Stir Welding - Daffa Aulian Rahmat; Viktor Naubnome (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
This research investigates the effect of feed rate on the mechanical and structural properties of friction stir welding (FSW) of aluminium 6061. This method is important because FSW is an environmentally friendly and energy efficient welding technique for applications on aluminium materials and its alloys. The feed rates used are 60 mm/min, 90 mm/min and 120 mm/min. Hardness, tensile and microstructure tests are carried out to understand how feed rate affects material properties. The hardness value of the material also shows a trend that is in line with the tensile strength, with variations in the feed rate parameter having a significant effect on the hardness in the weld metal area, the heat affected zone (HAZ) and the base metal